Lyapunov-based Stability Analysis for Conveying Fluid Pipe with Nonlinear Energy Sink. Issue 2 (2020) - Duan, Nan; Wu, Yuhu; Sun, Xi-Ming; Zhong, Chongquan; Wang, Wei
Abstract: This paper considers the stability of a conveying fluid pipe with nonlinear energy sink (NES), which is a passive vibration controller. Based on the Galerkin approximation method, the fourth-order partial differential equation (PDE) model of the conveying fluid pipe-NES system is converted into an ordinary differential equation (ODE) form. Then, based on the first order characterization of convexity and energy disturbances technique under the framework of Lyapunov stability theory, global exponential stability of the conveying fluid pipe-NES system is obtained.